115k views
4 votes
Sonji correctly added 2p+1/p-8 and 3p-3/4p and got 8p^2+4p+3p-27p+24/(p-8)(4p). What is the simplified sum?

2 Answers

3 votes

Answer:


(11p^2-23p+24)/(4p(p-8))

Explanation:

Given expression,


(2p+1)/(p-8)+(3p-3)/(4p)


=(4p(2p+1)+(p-8)(3p-3))/(4p(p-8))


=(8p^2+4p+3p^2-24p-3p+24)/(4p(p-8))

By combining like terms,


=(11p^2-23p+24)/(4p(p-8))

Since, further simplification is not possible because numerator is not the perfect square trinomial,

Hence, the required simplified sum is,


(11p^2-23p+24)/(4p(p-8))

User Tkrajcar
by
4.5k points
4 votes

Answer:

The simplified sum is
(11p^(2)-23p+24)/((p-8)4p)

Step-by-step explanation:

we have


(2p+1)/(p-8)+(3p-3)/(4p)=(4p(2p+1)+(p-8)(3p-3))/((p-8)4p)\\ \\=(8p^(2)+4p+3p^(2)-3p-24p+24)/((p-8)4p)\\ \\ =(11p^(2)-23p+24)/((p-8)4p)